(untitled) (Legal journal - Research in Legal and Social Sciences, 2020)
Dignity as the base of human nature, is the foundation of fundamental invididual and collective rights. In both categories, the right to life and health stand out, since they are closely related to each other, in that both ensure the wellbeing of each citizen of the Republic. To reach the coverage of this pair of prerrogatives by means of public policies, specially in jurisdictional matter, remains a challange in many areas such as: life quality, health and security system, fight against poverty, full assistance to vulnerable groups such as children, adolescents and senior adults. The Public Ministry, as autonomous institution that represents the society towards the judicial body, has played, in the democratic era, a key role in the pursuit of public criminal proceedings against crimes and offenses that undermine the fundamental legal rights showed in this article, including trafficking of drugs, homicides, violence based on gender, torture, abduction, human trafficking, and other crimes against life and health.